Case report: eosinophilic myocarditis in hypereosinophilic syndrome: a journey to heart transplantation - Sharma, Shriya; Desai, Smruti; Leoni, Juan; Paghdar, Smit; Ruiz, Jose; Goswami, Rohan (Frontiers in Immunology, 2024)
Introduction Hypereosinophilic Syndrome (HES) is a rare disorder characterized by persistent elevation of eosinophils, leading to multi-organ infiltration and damage. Eosinophilic Myocarditis (EM) is one of its severe complications contributing significantly to morbidity and mortality. Herein, we describe the diagnostic and therapeutic challenges of EM, emphasizing the significance of early recognition and multidisciplinary management. Case Presentation A 51-year-old female with a history of EM, heart failure, and peripheral eosinophilia presented with NYHA class 3b symptoms. Laboratory findings revealed elevated peripheral eosinophil count, NT-Pro BNP, and characteristic electrocardiogram abnormalities. Imaging studies confirmed biventricular thrombi and myocardial abnormalities consistent with EM. Treatment involved Solu-Medrol for HES and heparin for ventricular thrombi, leading to initial clinical improvement. However, refractory heart failure necessitated urgent heart transplantation. Discussion EM, an under-recognized complication of HES, poses diagnostic and management challenges. Management includes standard heart failure treatments, steroids, and emerging therapies like Mepolizumab. Early diagnosis and aggressive management are pivotal for improving outcomes in this rare and potentially fatal condition. Conclusion Advancements in the detection of complications, surgical management, and therapeutic options have improved outcomes in HES. Ongoing research is essential to further understand and address the diagnostic and therapeutic challenges of HES and EM.